Identification of necroptosis-related genes for predicting prognosis and exploring immune infiltration landscape in colon adenocarcinoma - Wang, Ye; Lin, Ming-gui; Meng, Lei; Chen, Zhang-ming; Wei, Zhi-jian; Ying, Song-cheng; Xu, Aman (Frontiers in Oncology, 2022)
Background: Necroptosis is a recently discovered form of cell death which plays an important role in the occurrence and development of colon adenocarcinoma (COAD). Our study aimed to construct a risk score model to predict the prognosis of patients with COAD based on necroptosis-related genes. Methods: The genes expression data of COAD and normal colon samples were obtained from the Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx). Least absolute shrinkage and selection operator (LASSO) Cox regression analysis was used to calculate the risk score based on prognostic necroptosis-related differentially expressed genes (DEGs). Based on the risk score, patients were classified into high- and low-risk groups. Then, nomogram models were built based on the risk score and clinicopathological features. Otherwise, the model was verified in Gene Expression Omnibus (GEO) database. Additionally, tumor microenvironment (TME) and the level of immune infiltration were evaluated by “ESTIMATE” and single sample gene set enrichment analysis (ssGSEA). Functional enrichment analysis was carried out to explore the potential mechanism of necroptosis in COAD. Finally, the effect of necroptosis on colon cancer cells was explored through CCK8 and transwell assays. The expression of necroptosis-related genes in colon tissues and cells treated with necroptotic inducers (TNFα) and inhibitors (NEC-1) was evaluated by quantitative real-time polymerase chain reaction (qRT-PCR). Results: The risk score was an independent prognostic risk factor in COAD. The predictive value of the nomogram based on the risk score and clinicopathological features was superior to TNM staging. The effectiveness of the model was well validated in GSE152430. Immune and stromal scores were significantly elevated in the high-risk group. And necroptosis may influence the prognosis of COAD via influencing cancer immune response. In vitro experiments, the inhibition of necroptosis can promote the proliferation and invasion ability. Finally, the differential expression of necroptosis-related genes in 16 paired colon tissues and colon cancer cells was found. Conclusion: A novel necroptosis-related genes signature for prognosis forecasting of COAD has been constructed, which possesses favorable predictive ability, which offers ideas to the necroptosis-associated development of COAD. Keywords: TCGA, necroptosis, colon adenocarcinoma, prognosis model, immune